Izmir grape polyphenol oxidase (Vitis vinifera L.):: Partial purification and some kinetic properties - Onez, Zehra; Karakus, Emine; Pekyardimci, Sule (WILEY, 2008)
Polyphenol oxidase (PPO) was extracted from the Izmir grape fruit (Vitis vinifera L.) and its characteristics were studied. The PPO enzyme was purified 2.2-fold by (NH4)(2)SO4 precipitation and 26.1-fold by gel filtration chromatography. This partially purified enzyme obtained from dialysis migrated as one band with catechol substrate, four bands with Coomassie brilliant R-250 (NATIVE-PAGE) native system and as six bands of 34, 30, 22, 18, 16 and 15 kDa on sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The sample obtained from dialysis after ammonium sulfate precipitation was used for the characterization of partially purified enzyme. Substrate specificity experiments were carried out with catechol, 4-methyl catechol, L-tyrosine, pyrogallol, p-cresol, gallic acid and caffeic acid. Michael-Menten constant and maximum velocity values were 3.65 mM and 1,971.6 Delta A/dak, respectively, with catechol substrate. Optimum pH for the PPO enzyme were determined at 7.2, 7.0, 7.4, 7.2, 6,4, 6.7 and 5.7 using catechol, 4-methyl catechol, L-tyrosine, pyrogallol, p-cresol, gallic acid and caffeic acid substrates, respectively. Optimum temperature for maximum PPO activity was 25C for catechol. Heat inactivation studies showed a significiant decrease in enzymatic activity at temperatures above 45C. Activation energy was calculated to be 12.4 kcal/mol. The most potent inhibitors for the grape PPO were thiourea, sodium diethyldithiocarbamate and sodium azide. Inhibition constants were calculated for L-ascorbic acid, L-cysteine and beta-mercaptoethanol at the optimum pH of PPO activity.
Keywords: ACTIVATION; INACTIVATION; CHROMATOGRAPHY; PROTEINS; JUICE; PPO; Biochemistry & Molecular Biology; Food Science & Technology